(untitled) (Revista Tempo e Argumento, 2017)
This article takes as its starting point a text by Reinhart Koselleck on the theme of memory, which analyzes supposed discontinuities between primary experiences and secondary forms of remembrance. Although this is a specific text and we do not intend to see its statements as foundations of a supposed author’s thought as a whole, we point out some potential relations with theses found in his other works. Then, some of his formulations are brought to a rather strictly epistemological level and compared to theses by authors such as Aleida Assmann, Joël Candau, Hannah Arendt, and Paul Ricoeur. The goal, in this case, is just mapping some problems regarded as relevant when dealing with the relations between history, memory, truth, and justice, without any ambition of solving them. Keywords: Koselleck, Reinhart; Memory; Experience.